New Velocity Measurements of NGC 5128 Globular Clusters Out to 130 kpc: Outer Halo Kinematics, Substructure, and Dynamics - Allison K. Hughes; David J. Sand; Anil Seth; Jay Strader; Chris Lidman; Karina Voggel; Antoine Dumont; Denija Crnojević; Mario Mateo; Nelson Caldwell; Duncan A. Forbes; Sarah Pearson; et al. (The Astrophysical Journal, 2023)
We present new radial velocity measurements from the Magellan and the Anglo-Australian Telescopes for 175 previously known and 121 newly confirmed globular clusters (GCs) around NGC 5128, the nearest accessible massive early-type galaxy at D = 3.8 Mpc. Remarkably, 28 of these newly confirmed GCs are at projected radii $\gt 50^{′} $ (≳54 kpc), extending to ∼130 kpc, in the outer halo where few GCs had been confirmed in previous work. We identify several subsets of GCs that spatially trace halo substructures that are visible in red giant branch star maps of the galaxy. In some cases, these subsets of GCs are kinematically cold, and may be directly associated with and originate from these specific stellar substructures. From a combined kinematic sample of 645 GCs, we see evidence for coherent rotation at all radii, with a higher rotation amplitude for the metal-rich GC subpopulation. Using the tracer mass estimator, we measure a total enclosed mass of 2.5 ± 0.3 × 10 ^12 M _⊙ within ∼120 kpc, an estimate that will be sharpened with forthcoming dynamical modeling. The combined power of stellar mapping and GC kinematics makes NGC 5128 an ongoing keystone for understanding galaxy assembly at mass scales inaccessible in the Local Group.